Treatments for intrusive luxation in permanent teeth: a systematic review and meta-analysis - Costa, L. A. [UNESP]; Ribeiro, C. C.C.; Cantanhede, L. M.; Santiago Júnior, J. F.; de Mendonça, M. R. [UNESP]; Pereira, A. L.P. (Elsevier, 2017)
Intrusive luxation is a severe form of dental trauma and there is no consensus regarding its management for permanent teeth. A systematic review and meta-analysis was performed to identify the appropriate treatment for teeth with intrusive luxation. The PubMed/MEDLINE, Embase, US Clinical Trials, and ISRCTN Registry electronic databases were used to search for articles in English and unpublished studies without a date limit. Eligible studies evaluated periodontal results (root resorption as the primary outcome; marginal bone defects and/or pulpal changes as secondary outcomes) after spontaneous re-eruption (SRE), orthodontic repositioning (ORP), or surgical repositioning (SRP) for patients with one or more traumatically intruded permanent teeth. Risk ratios with 95% confidence intervals were used to compare treatments. The meta-analysis revealed no significant difference (P > 0.05) between SRP and SRE for root resorption. For secondary outcomes, SRE was significantly better than SRP and ORP (P < 0.05). Subgroup analyses showed no significant differences among treatments in teeth with completely formed roots (P > 0.05) and a better prognosis when SRE was performed in teeth with incompletely formed roots (P < 0.05). The available evidence does not allow us to conclude on the best treatment for traumatically intruded teeth. More reliable evidence is needed.
Keywords: dental trauma; dentition; meta-analysis; permanent; tooth injuries